Age-Related and Sex Differences in Visuospatial Working Memory and Its Association with Math Achievement: Insights from Span, Accuracy, and RT in Corsi Block Tapping Test - Sergey B. Malykh; Yulia V. Kuzmina (Psychology in Russia: State of Art)
Background. Visuospatial working memory (VSWM) is critical for academic achievement, particularly in mathematics. The Corsi Block-Tapping Test (CBTT) is one of the most widely used tools to assess VSWM, traditionally relying on span length as the primary performance indicator. However, recent research suggests that additional metrics, such as accuracy and reaction time (RT), may offer complementary insights. Despite this, RT remains underexplored in studies examining VSWM development and its links to academic outcomes such as math performance. Objective. To investigate age- and sex-related changes in VSWM using CBTT accuracy, span, and RT, and to examine how these metrics relate to math achievement across school grades and sexes. Design. Data were collected from 2,749 Russian pupils (53% girls), aged 10 to 18 years (M = 13.89, SD = 2.08), enrolled in grades 5 to 11 in two regions (Nizhny Novgorod and Irkutsk). Regression analysis was applied to three indicators of CBTT and math achievement that was measured by average school grades. Results. CBTT accuracy increased and RT decreased from grades 5 to 8, then both increased post-grade 9, suggesting a developmental shift. Accuracy predicted math grades in grades 5–9 but not later; RT was a stable negative predictor across all grades. Sex did not moderate VSWM–math associations, though girls showed greater RT efficiency in late adolescence. Conclusion. VSWM develops along non-linear trajectories that differ by metric. Multi-indicator assessment is essential, and school grades should be interpreted with caution as proxies for math ability.